A LESBIAN REPRESENTATION IN KIDS' YOUTUBE SHOWS ON THE GECKO'S GARAGE CHANNEL - Derivanti, Azizah; Pratama, Amartheo Rifi (Journal of Social Political Sciences, 2023)
Research title by Baby Truck Family Valentines Day on the Gecko's Garage YouTube channel uses 2 semiotic analyzes namely Roland Barthes and Charles Sanders Pierce. The aim of this research is to find representations of sexual deviance in young children's broadcasts. In this video, researchers found LGBTQR+ elements, especially lesbian representation. This is shown starting from parents who are women and girls (not men and women), then daughters join in celebrating Valentine's Day. This video is not suitable for broadcast in Indonesia because it is very contrary to the norms that exist in Indonesia. If children watch this animation, there are concerns that they will follow LGBTQ+ activists in the future. Or the least impact is tolerating the presence of LGBTQ+ activists, especially in this case, lesbians around them.